A 34-Week Size Uterus with a Complete Hydatidiform Mole: Hook Effect and Severe Anemia with No Vaginal Bleeding - Rodney McLaren; Vijaya Bayya; Mohamad Irani (Case Reports in Obstetrics and Gynecology)
Complete hydatidiform mole is an abnormal pregnancy that usually presents with vaginal bleeding and markedly elevated serum ß-hCG levels. We report a rare case of complete hydatidiform mole occurring in a 16-year-old nulligravid who presented with a 34-week size uterus and a relatively low serum ß-hCG level (722 IU/L)—likely related to the “hook effect”—and severe anemia (hemoglobin: 6.1 g/dL) despite the absence of vaginal bleeding. She also reported right flank pain and was diagnosed with moderate right hydronephrosis owing to the compression exerted by the enlarged uterus on the right ureter. The patient received a total of 6 units of packed red blood cells and was managed by dilation and evacuation followed by serial monitoring of serum ß-hCG levels. Therefore, complete mole can present with symptoms related to an enlarged uterus and severe anemia before the occurrence of vaginal bleeding. It is also important to note that a negative urine pregnancy test or relatively low serum ß-hCG level should prompt repeating the measurement on diluted sample to prevent the “hook effect.”